Język i kultura w przekładzie tekstów specjalistycznych - Piotrowski, Sebastian; Sadowska-Dobrowolska, Katarzyna (Neofilolog, 2023)
This study explores the link between language and culture in the context of translating specialist texts. The starting point is the assumption that each text contains a cultural element, even if it is “only” a professional text. The illustration of the theoretical considerations is a comparative analysis of translations (from French into Polish) of press articles in the field of economics. The analysis of selected press materials shows that their cultural value is not a peripheral phenomenon, but constitutes an important sense-creating element. In the process of their translation, the translator's tasks include not only changing the original linguistic structures, but also changing the cultural perspective embedded in the text. The carriers of the cultural point of view are both single lexical units, as well as linguistic constructions and complex conceptual networks. Based on the research, the authors conclude that it seems particularly important to sensitize students to respect the genre standards of the target language and to understand the need to reconceptualize the original conceptual metaphor and change the deictic perspective of the text.